Synthesis of highly substituted fluorenones via metal-free TBHP-promoted oxidative cyclization of 2-(aminomethyl)biphenyls. Application to the total synthesis of nobilone - Jourjine, Ilya A. P.; Zeisel, Lukas; Krauß, Jürgen; Bracher, Franz (Beilstein Journal of Organic Chemistry, 2021)
Highly substituted fluorenones are readily prepared in mostly fair to good yields via metal- and additive-free TBHP-promoted cross-dehydrogenative coupling (CDC) of readily accessible N-methyl-2-(aminomethyl)biphenyls and 2-(aminomethyl)biphenyls. This methodology is compatible with numerous functional groups (methoxy, cyano, nitro, chloro, and SEM and TBS-protective groups for phenols) and was further utilized in the first total synthesis of the natural product nobilone.
Keywords: cross-dehydrogenative coupling; cyclization; fluorenones; nobilone; total synthesis

(untitled) - Talapatra, S. K.; Bose, S.; Mallik, A. K.; Talapatra, B. (Tetrahedron, 1985)

(untitled) - Wang, S.; Wen, B.; Wang, N.; Liu, J.; He, L. (Arch. Pharmacal Res., 2009)

(untitled) - Wang, X.-L.; Liu, B.-R.; Chen, C.-K.; Wang, J.-R.; Lee, S.-S. (Fitoterapia, 2011)

(untitled) - Sargent, M. V. (J. Chem. Soc., Perkin Trans. 1, 1987)

(untitled) - Fan, C.; Wang, W.; Wang, Y.; Qin, G.; Zhao, W. (Phytochemistry, 2001)

(untitled) - Zhang, X.; Xu, J.-K.; Wang, J.; Wang, N.-L.; Kurihara, H.; Kitanaka, S.; Yao, X.-S. (J. Nat. Prod., 2007)

(untitled) - Si, K.; Liu, J.; He, L.; Li, X.; Gou, W.; Liu, C.; Li, X. (J. Pharmacol. Sci., 2010)

(untitled) - Hu, Q.-F.; Zhou, B.; Huang, J.-M.; Gao, X.-M.; Shu, L.-D.; Yang, G.-Y.; Che, C.-T. (J. Nat. Prod., 2013)

(untitled) - Pan, H.-L.; Fletcher, T. L. (J. Med. Chem., 1965)

(untitled) - Sill, A. D.; Albrecht, W. L.; Andrews, E. R.; Fleming, R. W.; Horgan, S. W.; Roberts, E. M.; Sweet, F. W. (J. Med. Chem., 1973)

(untitled) - Morgan, G. T.; Stewart, J. (J. Chem. Soc., 1931)

(untitled) - Ekins, S.; Lane, T. R.; Madrid, P. B. (Pharm. Res., 2020)

(untitled) - Alcaro, S.; Arena, A.; Di Bella, R.; Neri, S.; Ottanà, R.; Ortuso, F.; Pavone, B.; Vigorita, M. G. (ARKIVOC, 2004)

(untitled) - Zhou, D.; Tuo, W.; Hu, H.; Xu, J.; Chen, H.; Rao, Z.; Xiao, Y.; Hu, X.; Liu, P. (Eur. J. Med. Chem., 2013)

(untitled) - Perry, P. J.; Read, M. A.; Davies, R. T.; Gowan, S. M.; Reszka, A. P.; Wood, A. A.; Kelland, L. R.; Neidle, S. (J. Med. Chem., 1999)

(untitled) - Kulkarni, A. P.; Kong, X.; Jenekhe, S. A. (J. Phys. Chem. B, 2004)

(untitled) - Leclerc, M. (J. Polym. Sci., Part A: Polym. Chem., 2001)

(untitled) - Qin, C.; Islam, A.; Han, L. (J. Mater. Chem., 2012)

(untitled) - Craig, M. R.; de Kok, M. M.; Hofstraat, J. W.; Schenning, A. P. H. J.; Meijer, E. W. (J. Mater. Chem., 2003)

(untitled) - Wong, K.-T.; Chen, Y.-M.; Lin, Y.-T.; Su, H.-C.; Wu, C.-c. (Org. Lett., 2005)

(untitled) - Sanchez, J. C.; Trogler, W. C. (J. Mater. Chem., 2008)

(untitled) - Tang, J.; Zhao, S.; Wei, Y.; Quan, Z.; Huo, C. (Org. Biomol. Chem., 2017)

(untitled) - Moorthy, J. N.; Samanta, S. (J. Org. Chem., 2007)

(untitled) - Danheiser, R. L.; Gould, A. E.; de la Pradilla, R. F.; Helgason, A. L. (J. Org. Chem., 1994)

(untitled) - Rodríguez, D.; Martínez-Esperón, M. F.; Navarro-Vázquez, A.; Castedo, L.; Domínguez, D.; Saá, C. (J. Org. Chem., 2004)

(untitled) - Kumar, D. R.; Satyanarayana, G. (ChemistrySelect, 2018)

(untitled) - Kaiser, R. P.; Caivano, I.; Kotora, M. (Tetrahedron, 2019)

(untitled) - Kumar, D. R.; Kishore, D. R.; Satyanarayana, G. (SynOpen, 2018)

(untitled) - Olah, G. A.; Mathew, T.; Farnia, M.; Prakash, G. K. S. (Synlett, 1999)

(untitled) - Zhang, X.; Ji, X.; Jiang, S.; Liu, L.; Weeks, B. L.; Zhang, Z. (Green Chem., 2011)

(untitled) - Pünner, F.; Schieven, J.; Hilt, G. (Org. Lett., 2013)

(untitled) - Fu, J. M.; Zhao, B. P.; Sharp, M. J.; Snieckus, V. (J. Org. Chem., 1991)

(untitled) - Wang, W.; Snieckus, V. (J. Org. Chem., 1992)

(untitled) - Shi, Z.; Glorius, F. (Chem. Sci., 2013)

(untitled) - Mishra, K.; Pandey, A. K.; Singh, J. B.; Singh, R. M. (Org. Biomol. Chem., 2016)

(untitled) - Laha, J. K.; Patel, K. V.; Dubey, G.; Jethava, K. P. (Org. Biomol. Chem., 2017)

(untitled) - Laha, J. K.; Jethava, K. P.; Patel, S.; Patel, K. V. (J. Org. Chem., 2017)

(untitled) - Ravi Kumar, D.; Satyanarayana, G. (Org. Lett., 2015)

(untitled) - Sarkar, S.; Tadigoppula, N. (RSC Adv., 2014)

(untitled) - de Costa, B. R.; Radesca, L. (Synthesis, 1992)

(untitled) - Badea, I.; Cotelle, P.; Catteau, J.-P. (Synth. Commun., 1994)

(untitled) - Bjørsvik, H.-R.; Fontana, F.; Liguori, L.; Minisci, F. (Chem. Commun., 2001)

(untitled) - Gong, J.-L.; Qi, X.; Wei, D.; Feng, J.-B.; Wu, X.-F. (Org. Biomol. Chem., 2014)

(untitled) - Tanaka, H.; Oisaki, K.; Kanai, M. (Synlett, 2017)

(untitled) - Hu, Y.; Zhou, L.; Lu, W. (Synthesis, 2017)

(untitled) - Recupero, F.; Punta, C. (Chem. Rev., 2007)

(untitled) - Zheng, Z.; Dian, L.; Yuan, Y.; Zhang-Negrerie, D.; Du, Y.; Zhao, K. (J. Org. Chem., 2014)

(untitled) - Nauth, A. M.; Orejarena Pacheco, J. C.; Pusch, S.; Opatz, T. (Eur. J. Org. Chem., 2017)

(untitled) - Li, C.-J. (Acc. Chem. Res., 2009)

(untitled) - Ludwig, M.; Hoesl, C. E.; Höfner, G.; Wanner, K. T. (Eur. J. Med. Chem., 2006)

(untitled) - Huang, B.; Tian, H.; Lin, S.; Xie, M.; Yu, X.; Xu, Q. (Tetrahedron Lett., 2013)

(untitled) - Lin, M.; Wang, Z.; Fang, H.; Liu, L.; Yin, H.; Yan, C.-H.; Fu, X. (RSC Adv., 2016)

(untitled) - Cecchetto, A.; Minisci, F.; Recupero, F.; Fontana, F.; Franco Pedulli, G. (Tetrahedron Lett., 2002)

(untitled) - Wan, J.-C.; Huang, J.-M.; Jhan, Y.-H.; Hsieh, J.-C. (Org. Lett., 2013)

(untitled) - Wertz, S.; Leifert, D.; Studer, A. (Org. Lett., 2013)

(untitled) - Miller, R. A.; Hoerrner, R. S. (Org. Lett., 2003)

(untitled) - Wu, X.-F.; Gong, J.-L.; Qi, X. (Org. Biomol. Chem., 2014)

(untitled) - Edsall, R. J., Jr; Harris, H. A.; Manas, E. S.; Mewshaw, R. E. (Bioorg. Med. Chem., 2003)

(untitled) - Pan, W.; Hu, K.; Bai, P.; Yu, L.; Ma, Q.; Li, T.; Zhang, X.; Chen, C.; Peng, K.; Liu, W.; Sang, Z. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Kim, Y.; Tae, J.; Lee, K.; Rhim, H.; Choo, I. H.; Cho, H.; Park, W.-K.; Keum, G.; Choo, H. (Bioorg. Med. Chem., 2014)

(untitled) - Gracheva, I. A.; Svirshchevskaya, E. V.; Faerman, V. I.; Beletskaya, I. P.; Fedorov, A. Yu. (Synthesis, 2018)

Greene's Protective Groups in Organic Synthesis - Wuts, P. G. M.; Greene, T. W. (John Wiley & Sons, 2006)

(untitled) - Kamiya, M.; Kobayashi, H.; Hama, Y.; Koyama, Y.; Bernardo, M.; Nagano, T.; Choyke, P. L.; Urano, Y. (J. Am. Chem. Soc., 2007)

(untitled) - Bonin, H.; Delbrayelle, D.; Demonchaux, P.; Gras, E. (Chem. Commun., 2010)

(untitled) - Wang, Y.; Cai, W.; Tang, T.; Liu, Q.; Yang, T.; Yang, L.; Ma, Y.; Zhang, G.; Huang, Y.; Song, X.; Orband-Miller, L. A.; Wu, Q.; et al. (ACS Med. Chem. Lett., 2018)

(untitled) - Naysmith, B. J.; Furkert, D.; Brimble, M. A. (Tetrahedron, 2014)

(untitled) - Allin, S. M.; Barton, W. R. S.; Bowman, W. R.; McInally, T. (Tetrahedron Lett., 2001)

(untitled) - Miranda, L. D.; Cruz-Almanza, R.; Pavón, M.; Alva, E.; Muchowski, J. M. (Tetrahedron Lett., 1999)

(untitled) - Yorimitsu, H.; Nakamura, T.; Shinokubo, H.; Oshima, K.; Omoto, K.; Fujimoto, H. (J. Am. Chem. Soc., 2000)